Cell-based and multi-omics profiling reveals dynamic metabolic repurposing of mitochondria to drive developmental progression of Trypanosoma brucei - Doleželová, Eva; Kunzová, Michaela; Dejung, Mario; Levin, Michal; Panicucci, Brian; Regnault, Clément; Janzen, Christian J; Barrett, Michael P; Butter, Falk; Zíková, Alena (PLoS biology, 2020)
Mitochondrial metabolic remodeling is a hallmark of the Trypanosoma brucei digenetic life cycle because the insect stage utilizes a cost-effective oxidative phosphorylation (OxPhos) to generate ATP, while bloodstream cells switch to aerobic glycolysis. Due to difficulties in acquiring enough parasites from the tsetse fly vector, the dynamics of the parasite's metabolic rewiring in the vector have remained obscure. Here, we took advantage of in vitro-induced differentiation to follow changes at the RNA, protein, and metabolite levels. This multi-omics and cell-based profiling showed an immediate redirection of electron flow from the cytochrome-mediated pathway to an alternative oxidase (AOX), an increase in proline consumption, elevated activity of complex II, and certain tricarboxylic acid (TCA) cycle enzymes, which led to mitochondrial membrane hyperpolarization and increased reactive oxygen species (ROS) levels. Interestingly, these ROS molecules appear to act as signaling molecules driving developmental progression because ectopic expression of catalase, a ROS scavenger, halted the in vitro-induced differentiation. Our results provide insights into the mechanisms of the parasite's mitochondrial rewiring and reinforce the emerging concept that mitochondria act as signaling organelles through release of ROS to drive cellular differentiation.
Keywords: transkriptom; Electrons; Mitochondria; adenosintrifosfát; Glucose; Cell Line; elektrony; Metabolomics; Oxidoreductases; reaktivní formy kyslíku; Cell Respiration; metabolomika; proteom; buněčné dýchání; Proline; signální transdukce; buněčná diferenciace; Transcriptome; transport elektronů; prolin; protozoální proteiny; glukosa; Plant Proteins; oxidoreduktasy; mitochondriální proteiny; Trypanosoma brucei brucei; Signal Transduction; oxidace-redukce; Mitochondrial Proteins; Electron Transport; Reactive Oxygen Species; metabolické sítě a dráhy; buněčné linie; Adenosine Triphosphate; membránový potenciál mitochondrií; Protozoan Proteins; Oxidation-Reduction; Proteome; Metabolic Networks and Pathways; Membrane Potential, Mitochondrial; mitochondrie; Cell Differentiation; rostlinné proteiny